Effect of vitamin C on inflammation and metabolic markers in hypertensive and/or diabetic obese adults: a randomized controlled trial - Ellulu MS; Rahmat A; Patimah I; Khaza'ai H; Abed Y (Dove Medical Press, 2015)
Mohammed S Ellulu,1 Asmah Rahmat,1 Ismail Patimah,2 Huzwah Khaza’ai,2 Yehia Abed3 1Department of Nutrition and Dietetics, 2Department of Biomedical Science, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Serdang, Malaysia; 3Faculty of Public Health, Al-Quds University, Gaza City, Palestine Background: Obesity is well associated as being an interfering factor in metabolic diseases such as hypertension and diabetes by increasing the secretion of proinflammatory markers from adipose tissue. Having healthy effects, vitamin C could work as an anti-inflammatory agent through its antioxidant capacity.Registration: Registration number: FPSK_Mac [13]04.Objective: The aim of the study reported here was to identify the effect of vitamin C on reducing the levels of inflammatory markers in hypertensive and/or diabetic obese adults.Subjects and methods: Sixty-four obese patients, who were hypertensive and/or diabetic and had high levels of inflammatory markers, from primary health care centers in Gaza City, Palestine, were enrolled into one of two groups in an open-label, parallel, randomized controlled trial. A total of 33 patients were randomized into a control group and 31 patients were randomized into an experimental group. The experimental group was treated with 500 mg vitamin C twice a day.Results: In the experimental group, vitamin C significantly reduced the levels of high-sensitivity C-reactive protein (hs-CRP), interleukin 6 (IL-6), fasting blood glucose (FBG), and triglyceride (TG) after 8 weeks of treatment (overall: P<0.001); no changes appeared in total cholesterol (TC). In the control group, there were significant reductions in FBG and TG (P=0.001 and P=0.026, respectively), and no changes in hs-CRP, IL-6, or TC. On comparing the changes in the experimental group with those in the control group at the endpoint, vitamin C was found to have achieved clinical significance in treating effectiveness for reducing hs-CRP, IL-6, and FBG levels (P=0.01, P=0.001, and P<0.001, respectively), but no significant changes in TC or TG were found.Conclusion: Vitamin C (500 mg twice daily) has potential effects in alleviating inflammatory status by reducing hs-CRP, IL-6, and FBG in hypertensive and/or diabetic obese patients. Keywords: obesity, hypertension, diabetes, anti-inflammatory, adiposity, Vitamin C